2023
DOI: 10.1055/a-2165-6388
|View full text |Cite
|
Sign up to set email alerts
|

Updated S3 Guideline “Sedation for Gastrointestinal Endoscopy” of the German Society of Gastroenterology, Digestive and Metabolic Diseases (DGVS) – June 2023 – AWMF-Register-No. 021/014

Till Wehrmann,
Andrea Riphaus,
Alexander J. Eckardt
et al.

Abstract: This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.1 The recommendation grade and the level of evidence are only specified for evidence-based recommendations. For expert consensusbased recommendations, the grading is done via we recommend/we suggest/may be considered and via the description given in the table.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 523 publications
(822 reference statements)
0
1
0
Order By: Relevance
“… 46 47 The updated guideline of German indicated that patients with ASA class III or higher have an increased risk of complications during sedation. 51 Therefore, the future conclusion of our study should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 83%
“… 46 47 The updated guideline of German indicated that patients with ASA class III or higher have an increased risk of complications during sedation. 51 Therefore, the future conclusion of our study should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 83%